Cessation of oral anticoagulants in antiphospholipid syndrome. (October 2017) - Comarmond, C; Jego, P; Veyssier-Belot, C; Marie, I; Mekinian, A; Elmaleh-Sachs, A; Leroux, G; Saadoun, D; Oziol, E; Fraisse, T; Hyvernat, H; Thiercein-Legrand, M-F; et al.
Objective: To study the outcome of patients with antiphospholipid syndrome (APS) after oral anticoagulant treatment cessation. Methods: We performed a retrospective study of patients with APS experiencing cessation of oral anticoagulant and enrolled in a French multicentre observational cohort between January 2014 and January 2016. The main outcome was the occurrence of recurrent thrombotic event after oral anticoagulation cessation. Results: Forty four APS patients interrupted oral anticoagulation. The median age was 43 (27–56) years. The median duration of anticoagulation was 21 (9–118) months. Main causes of oral anticoagulant treatment cessation were switch from vitamin K antagonists to aspirin in 15 patients, prolonged disappearance of antiphospholipid antibodies in ten, bleeding complications in nine and a poor therapeutic adherence in six. Eleven (25%) patients developed a recurrent thrombotic event after oral anticoagulation cessation, including three catastrophic APS and one death due to lower limb ischemia. Antihypertensive treatment required at time of oral anticoagulants cessation seems to be an important factor associated with recurrent thrombosis after oral anticoagulant cessation (15.2% in patients with no relapse versus 45.5% in patients with recurrent thrombosis, p = 0.038). Oral anticoagulant treatment was re-started in 18 (40.9%) patients. Conclusion: The risk of a new thrombotic event in APS patients who stopped their anticoagulation is high, even in those who showed a long lasting disappearance of antiphospholipid antibodies. Except for the presence of treated hypertension, this study did not find a particular clinical or biological phenotype for APS patients who relapsed after anticoagulation cessation. Any stopping of anticoagulant in such patients should be done with caution.